New unavailable names in Buprestidae (Coleoptera) and a short comment on the electronic publication of new names - Bílý, Svatopluk; Volkovitsh, Mark G. (Zootaxa, 2017)
Since the catalogue of Buprestoidea was published (Bellamy, 2008–2009) we have been adding new taxa into the printed copy in the National Museum, Prague. During this work we have found some questionable descriptions which were published in the electronic publication “Procrustomachia” which has no official status and does not meet the requirements for the publication of scientific names in zoology; the names published in this way are unavailable according to the Code (ICZN, 1999, 2012). The situation is discussed in the following text.